Analysis of Relevancy of Local Culture Wisdom in Salt Production with Analytical Chemistry Subject in Order to Develop Instruments for Integrated Etnochemistry Lecture - Muti'ah Muti'ah; Jackson Siahaan; Yayuk Andayani; Mukhtar Haris; Supriadi Supriadi (Postgraduate, University of Mataram, 2023)
Characteristic of Chemistry learning which is integrated with etnochemistry is the existing of local culture wisdom aspects as a learning media, as a learning source, or as a learning method to comprehend chemistry concepts. This descriptive research aims to analyse the relevance of local culture wisdom with Analytical Chemistry subject which is integrated with etnochemistry in production of salt in order to develop learning instruments based on Problem Based Learning (PBL) learning method. The objects of the research are local culture wisdom in production of table salt (in Pijot village, Sub-district of Keruak, Distric of East Lombok, West Nusa Tenggara Province, Indonesia) and Analytical Chemistry subject. Data is collected from documents and interview and then being analysed descriptively. The results showed that (1) There is a relevancy of local culture wisdom element in production of salt with any topic in Analytical Chemistry subject, (2) Lecture instruments of Analytical Chemistry subject which is integrated with etnochemistry could be developed by including sea water, salt, and bittern water as learning media in class lecture and in practical work in laboratory, and salt crystallization process as learning source, (3) Lecture instruments of Analytical Chemistry subject which is integrated with etnochemistry based on PBL method could be developed by including real problem in society as a way to improve quality of salt so it appropriate with SNI standard. (SNI = Standar Nasional Indonesia: Indonesia National Standard).